2006
DOI: 10.1111/j.1524-4725.2005.31046
|View full text |Cite
|
Sign up to set email alerts
|

Metastasizing Atypical Fibroxanthoma (Cutaneous Malignant Histiocytoma): Report of Five Cases

Abstract: The metastatic potential of AFX may be underestimated. LN-2 staining may be a useful marker in identifying more aggressive tumor behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 19 publications
2
69
0
Order By: Relevance
“…Lazova et al [5] retrospectively examined 20 MFH cases and 20 AFX cases and reported that 90% of the MFH cases were positive for CD74, whereas 90% of the AFX cases were negative for CD74. It is noteworthy that CD74-positive AFX tends to have a more aggressive behavior [6]. Positivity of CD74 in our case supports the diagnosis of MFH.…”
Section: Discussionsupporting
confidence: 76%
“…Lazova et al [5] retrospectively examined 20 MFH cases and 20 AFX cases and reported that 90% of the MFH cases were positive for CD74, whereas 90% of the AFX cases were negative for CD74. It is noteworthy that CD74-positive AFX tends to have a more aggressive behavior [6]. Positivity of CD74 in our case supports the diagnosis of MFH.…”
Section: Discussionsupporting
confidence: 76%
“…CD74 expression has also been found in nonhematologic malignancies, including gastric (31), renal (32), non -small cell lung (33), and thymic epithelium neoplasms (34), certain types of sarcoma (fibrous histiocytoma; ref. 35), and atypical fibroxanthoma, an unusual malignant fibrohistiocytic tumor of sun-damaged skin (36). CD74 expression in many of these cancers has been suggested to be a prognostic factor, with higher relative rates of CD74 behaving as a marker of tumor progression or poor clinical outcome (37).…”
Section: Cd74 Molecule: Structure Function and Expressionmentioning
confidence: 99%
“…7 Another patient developed localized cutaneous metastases of the scalp. 8 In a report by Cooper and colleagues, 9 they describe five patients who developed distant metastases. These patients all had a history of aggressive cutaneous malignancies or other noncutaneous malignancies.…”
Section: Discussionmentioning
confidence: 98%